Odpowiedzi

Najlepsza Odpowiedź!
2010-04-14T20:51:14+02:00
A)4x² -4x+1=0
(2x-1)²=0 x = 1/2

b)x² -14x+49=0
(x-7)²=0 x = 7

c)9x² -6x+1 =0
(3x-1)²=0 x = 1/3
2010-04-14T20:51:51+02:00
A)(2x-1)²=0 czyli x=1/2
b)(x-7)²=0 czyli x=7
c)(3x-1)²=0 czyli x=1/3
2010-04-14T20:52:21+02:00

a)4x² -4x+1=0
a= 4 b= -4 c=1
Δ=b²-4ac
Δ=16-16
Δ=0

x= -b przez 2a czyli 4przez 8
czyli 1/2

b)x² -14x+49=0
a=1 b= -14 c=49
Δ=b²-4ac
Δ=196-196
Δ=0

x= -b przez 2a czyli 14 przez 2 czyli 7


c)9x² -6x+1 =0
a=9 b= -6 c=1
Δ=b²-4ac
Δ=36-36
Δ=0

x= -b przez 2a czyli 6 przez 18